2018
DOI: 10.12707/riv18002
|View full text |Cite
|
Sign up to set email alerts
|

Self-report of pain intensity: correlation between children, parents, and nurses

Abstract: ]. Contribuição no artigo: pesquisa bibliográfica, colheita de dados, análise e discussão dos resultados, e redação do manuscrito. Recebido para publicação em: 17.01.18 Aceite para publicação em: 28.03.18 ARTIGO DE INVESTIGAÇÃO (ORIGINAL) RESEARCH PAPER (ORIGINAL) Resumo Enquadramento: Em pediatria são frequentes as situações clínicas em que existe impossibilidade de autoavaliação da dor e incerteza quanto à correlação existente entre a avaliação feita por pais e enfermeiros e o autorrelato da criança. Objetiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 11 publications
0
10
0
2
Order By: Relevance
“…Only a few studies have directly compared pain assessment scores between children, their guardians and medical professionals [ 14 , 15 , 16 , 17 , 18 ]. However, the current results are in agreement with previous studies indicating that the pain intensity experienced by children is higher than that reported by parents and nurses [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few studies have directly compared pain assessment scores between children, their guardians and medical professionals [ 14 , 15 , 16 , 17 , 18 ]. However, the current results are in agreement with previous studies indicating that the pain intensity experienced by children is higher than that reported by parents and nurses [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may result from greater experience with one’s own family member, including his/her typical sensory or emotional states, even though they are not always able to differentiate pain from these states [ 14 ]. Another study has also shown that there are no significant differences between parent and child pain scores, and that a nurse’s score is significantly lower than both groups [ 17 ]. Similarly, Hla et al have reported that, in communicative children following out-patient elective surgery, pain scores reported by the patients and their parents do not significantly differ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Um estudo desenvolvido com a participação de enfermeiros e pais, traz um comparativo de utilização da escala FLACC, uma vez que estes participantes conseguiriam realizar a avaliação, levandose em conta que o processo é baseado em comportamentos apresentados pelos pacientes, contudo o resultado da pesquisa mostrou que a escala foi melhor aceita e bem utilizada por parte da equipe de enfermagem, uma vez que estes são detentores de competências na área de avaliação (18) . Diante deste fato esta escala poderá ser aplicada pela equipe de enfermagem durante a internação hospitalar, utilizando-se do instrumento antes de qualquer procedimento doloroso e após intervenção não farmacológica e farmacológica.…”
Section: Discussionunclassified
“…Estudo realizado após a aplicação de anestésico tópico em 1.070 crianças antes de punção venosa pelos enfermeiros evidenciou diminuição da dor. Neste mesmo estudo observou-se que a partir de um ensaio clínico randomizado controlado com 80 crianças verificou-se estatisticamente a redução da dor após aplicada a EVA, demonstrando desta forma maior satisfação e adequação do processo doloroso por parte da criança (18) .…”
Section: Discussionunclassified